The association of weather, temperature, and holidays on pediatric maxillofacial trauma. Issue 5 (22nd September 2020) - Rabbani, Cyrus C.; Kao, Richard; Shin, Timothy J.; Burgeson, Jack E.; Ting, Jonathan Y.; Sim, Michael W.; Shipchandler, Taha Z.
Abstract: Objective: To evaluate the association of weather, seasons, months and holidays on the frequency and pattern of pediatric facial fractures. Methods: Retrospective review of pediatric patients treated for facial fractures at two Level I trauma centers in a midsize Midwestern US city over a 5‐year period. Patients were included only if presentation was within 3 hours of inciting trauma, transfers from other facilities were excluded. Demographic characteristics, fracture patterns, operative interventions, weather data, and local public school schedules were acquired and associations were analyzed with unpaired t tests, χ 2, multivariate and binomial regression model analyses. Results: Two hundred and sixty patients were included. The average age (SD) was 11.8 (5.0) years, with 173 males and 87 females. The highest distribution of presentations occurred in the summer season (35.0%), on weekends and holidays (58.1%), and when the weather was described as clear (48.5%). The most common mechanisms of injury were motor vehicle collisions (25.8%), followed by sports—(21.5%) and assault—(16.5%) related injuries. Mechanisms were significantly associated with certain fracture patterns. Older age was associated with fewer orbital fractures ( P < .01). Seventy‐five patients (28.8%) required operative intervention. Age was found to impact the likelihood of operative intervention (Exp( β ) = 1.081, P = .03) while weather, temperature, and mechanism did not. Conclusion: Pediatric facial fractures are linked to warmer weather with clear skies and warmer season. Age predicts some fracture patterns and need for operative intervention. These results can be used to inform public health interventions, policymaking, and trauma staffing. Level of Evidence: Level 2b (retrospective cohort). Abstract : A retrospective review of 260 pediatric facial trauma patients found an association between the incidence of facial fractures and warmer weather, clear skies, weekends or holidays, and mechanism of injury. Older age is associated with operative intervention. These results can be used to guide public health interventions, policymaking, and facial trauma resource allocation.